Indonesia: Guiding Fragile Communities Toward the SDGs Amid Economic, Socio-Political, and Religious Challenges - Muhammad Habibi Siregar; Dika Sahputra; Alfida; Ulpah Andayani; Fatimah Zuhrah (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study examines how Indonesia guides fragile communities toward achieving the Sustainable Development Goals (SDGs) amid persistent economic, socio-political, and religious challenges during the post-reform era. Theoretical framework: The study is grounded in the theoretical framework of social resilience, human security, and sustainable development, which emphasizes the interaction between institutional capacity, inclusive governance, and community adaptability in addressing structural vulnerabilities. Literature review: Previous studies have primarily discussed Indonesia’s democratic transition, poverty reduction, religious pluralism, and economic inequality as separate issues. However, limited scholarship has integrated these dimensions into a comprehensive transdisciplinary framework that explains how economic, political, and religious factors collectively influence the resilience of fragile communities and progress toward the SDGs. Method: This research employs a qualitative descriptive approach using document analysis of government reports, socioeconomic indicators, academic literature, and policy documents. The collected data were analyzed through thematic content analysis to identify patterns of interaction among governance, social welfare, economic recovery, and religious cohesion. Results: The findings demonstrate that Indonesia has made significant progress in democratic consolidation and poverty alleviation, yet substantial disparities remain across regions and vulnerable populations. Economic instability, political polarization, and socio-religious tensions continue to hinder equitable development and community resilience. The study further reveals that integrated governance combining inclusive public policies, equitable economic opportunities, social protection, and interreligious collaboration contributes substantially to strengthening fragile communities and accelerating SDG implementation. Implications: The implications suggest that policymakers should adopt transdisciplinary and community-centered strategies that simultaneously address structural inequality, democratic participation, and social cohesion. Novelty: The novelty of this study lies in proposing an integrated analytical framework linking economic resilience, democratic governance, and religious inclusiveness as interconnected determinants of fragile community empowerment, thereby offering a holistic perspective for advancing sustainable development in Indonesia and other pluralistic developing countries.